2007
DOI: 10.1161/hypertensionaha.106.082479
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Scavenger Receptor Class BI Gene Expression by Angiotensin II in Vascular Endothelial Cells

Abstract: Abstract-High-density lipoprotein mediates a normal physiological process called reverse cholesterol transport. In this process, a scavenger receptor of the B class (SR-BI)/human homologue of SR-BI, CD36, and LIMPII analogous-1 (hSR-BI/CLA-1) facilitates the cellular uptake of cholesterol from high-density lipoprotein. 1,2 In this process, HDL particles shuttle cholesterol from extrahepatic tissues to the liver for further metabolism and excretion. 1 Enhanced reverse cholesterol transport lowers total body ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Polymerase chain reactions (PCRs) were performed in a final volume of 20 ll in LightCycler (Roche, Mannheim, Germany) glass capillaries as described previously [13]. The reaction mixture consisted of 2 ll LightCycler-FastStart DNA Master SYBR Green I (Roche), 2.4 ll 25 mM MgCl2 stock solution, 11.6 ll sterile PCR-grade H 2 O, 2 ll of the cDNA template for each gene of interest, and 1 ll of 10 lM of each primer.…”
Section: Real-time Reverse-transcriptase-polymerase Chain Reactionmentioning
confidence: 99%
“…Polymerase chain reactions (PCRs) were performed in a final volume of 20 ll in LightCycler (Roche, Mannheim, Germany) glass capillaries as described previously [13]. The reaction mixture consisted of 2 ll LightCycler-FastStart DNA Master SYBR Green I (Roche), 2.4 ll 25 mM MgCl2 stock solution, 11.6 ll sterile PCR-grade H 2 O, 2 ll of the cDNA template for each gene of interest, and 1 ll of 10 lM of each primer.…”
Section: Real-time Reverse-transcriptase-polymerase Chain Reactionmentioning
confidence: 99%
“…SR-BI, a member of the CD36 family of proteins, is a multiligand receptor expressed on many cells, such as hepatocytes, macrophages, endothelial cells (including endothelium in veins 15 ) and platelets. 14,16,17,18 It plays an important role in protection against murine atherosclerosis.…”
mentioning
confidence: 99%
“…Known amounts of DNA were then diluted to provide standards and a regression curve of crossing points versus concentration generated with the LightCycler. GAPDH was used as a standard, as described in an earlier study [15].…”
Section: Real-time Reverse Transcriptase Pcrmentioning
confidence: 99%
“…Previous reports, including results from our laboratory [6,10], showed that cells take up CE from HDL by a selective non-endocytotic pathway. Our previous studies showed that the human homologue of SR-B1 (hSR-B1), CD36 and LIMPII Analogous-1 (CLA-1), functions as a receptor for HDL, similar to the mouse homologue [6,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%